Stepwise amplification of circularly polarized luminescence in indium-based metal halides by regulating their structural dimension - Cui-Mi Shi; Haolin Lu; Jin-Yun Wang; Guankui Long; Liang-Jin Xu; Zhong-Ning Chen (Nature Communications)
Abstract The pursuit of chiral lead-free metal halides with both high photoluminescence quantum yield (PLQY) and large luminescence dissymmetry factor (g lum) remains a priority for designing efficient circularly polarized light sources. However, a tradeoff exists between PLQY and g lum in chiral materials due to the mismatched electric (μ) and magnetic transition dipole moment (m). Herein, we address this contradiction and develop the efficient circularly polarized luminescence (CPL) emitters through structural dimension modulation. By tuning the size and polarization of chiral organic cations and employing the cascade cationic insertion strategy, 0D, 1D and 3D indium-based chiral metal halides are constructed. These hybrids exhibit self-trapped excitons emission with near-unity PLQY, while the |g lum| boosts exponentially from 10− 3 to nearly 10− 1 as the structural dimension increases from 0D to 3D, and the highest |g lum| of 0.89 × 10− 1 has been achieved. Structural analysis and theoretical calculation indicate the increased structural dimension promotes the formation of helical structure and enlarges magnetic transition dipole moment, thus resulting in improved CPL performance. Our research provides valuable insights on the relationship between g lum and structural dimension, thus will advance the development of efficient CPL-active materials for practical applications.